Manajemen Keamanan Kilang LNG (Liquefied Natural Gas) Tangguh Bintuni Papua - Edy Susanto; Lady Antira; Kevin Kevin; Edo Stanzah; Assyeh Annasrul Majid (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2023)
The security of a company's data information system security plan consists of a strategy and a division of responsibilities, the main objective of which is to reduce risks that have the potential to become a threat to the company's operations. British Petroleum in Indonesia is the Largest Offshore O & G’s operator, as well as the main distributor for domestic natural gas needs. The formulation is the Information Security Management System (ISMS) is a unified system that is structured based on a risk approach for the development, implementation, operation, supervision, maintenance and improvement of corporate information security. The research methodology reviewing literature studies covering BP Tangguh's security management. In its implementation, the company's security protection uses PDCA. British Petroleum (BP) ensures that the safety and identification aspects that are hazard and high risk have been taken directly, assessment security is a series of actions aimed at maintaining the security, integrity and confidentiality of the evaluation or assessment process. The security management system result at BP Tangguh, it is concluded the implementation and application of the security management system at BP Tangguh is optimal because it has a security management system that is very efficient, organized and has a clear legal basis.